2017
DOI: 10.1080/17457300.2016.1278235
|View full text |Cite
|
Sign up to set email alerts
|

Road safety perspectives among employees of a multinational corporation in urban India: local context for global injury prevention

Abstract: In rapidly developing economies, like urban India, where road traffic injury rates are among the world’s highest, the corporate workplace offers a non-traditional venue for road safety interventions. In partnership with a major multinational corporation with a large Indian workforce, this study aimed to elicit local employee perspectives on road safety to inform a global corporate health platform. The safety attitudes and behaviors of 75 employees were collected through self-report survey and focus groups in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Participants described the issue of laws not being enforced fairly and equally, for example affluent members of society are generally not penalised for violating the law. Similar findings were reported in other studies from India which also highlighted the issue of police accepting bribes for traffic offences [6,83]. Our study also showed that the violation of traffic laws particularly by law enforcement officials was believed to have a negative influence on the general public.…”
Section: Discussionsupporting
confidence: 91%
“…Participants described the issue of laws not being enforced fairly and equally, for example affluent members of society are generally not penalised for violating the law. Similar findings were reported in other studies from India which also highlighted the issue of police accepting bribes for traffic offences [6,83]. Our study also showed that the violation of traffic laws particularly by law enforcement officials was believed to have a negative influence on the general public.…”
Section: Discussionsupporting
confidence: 91%
“…Participants described the issue of laws not being enforced fairly and equally, for example a uent members of society are generally not penalised for violating the law. Similar ndings were reported in other studies from India which also highlighted the issue of police accepting bribes for tra c offences [39,66]. Our study also showed that the violation of tra c laws particularly by law enforcement o cials was believed to have a negative in uence on the general public.…”
Section: Discussionsupporting
confidence: 91%
“…32 In a survey among employees of a multinational corporation in urban India participants perceived that their local road environment was dangerous, there is inconsistent and unreliable enforcement of traffic laws and local traffic authority were viewed as lowpaid and often corrupt. 33 Our survey showed that awareness regarding the current state of road safety in India is limited. A similar survey conducted in a south Indian state showed participants had significantly low awareness with regards to alcohol and driving, use of seat belts and use of mobile phones; nearly two-third of the participants (68%) admitted to have crossed speed limits on multiple occasions.…”
Section: Discussionmentioning
confidence: 88%